First record of the genus Palpostilpnus Aubert (Ichneumonidae: Phygadeuontinae) from Vietnam, with descriptions of eight new species - Pham, Nhi Thi; Sheng, Mao-Ling; Park, Clara; Tran, Duong Dinh; Reshchikov, Alexey (Zootaxa, 2024)
Palpostilpnus Aubert, 1961 is a genus of the subfamily Phygadeuontinae (Hymenoptera: Ichneumonidae) with 17 currently recognized species from the Oriental and Australasian regions. In this paper, this genus is reported for the first time from Vietnam. Eight new species are described, comprising: P. cattienensis, P. hoanglienensis, P. incompletus, P. melanothoracicus, P. melinhensis, P. meovacensis, P. ngoclinhensis and P. taynguyenensis. Three species, P. maculata Sheng & Sun, 2013, P. pterodactylus Reshchikov, Santos, Liu, Barthélémy, 2019 and P. tamasek Reshchikov, Santos, Liu, Barthélémy, 2019 are recorded as new from the country. The key to the world species of Palpostilpnus by Reshchikov et al. (2019) is modified to include eight new species from Vietnam.